Pengaruh Lingkungan Sosial Terhadap Perkembangan Kepribadian Shyness Pada Mahasiswa - Siti Aisyah; Sri Nurhayati Selian (CV. Lentera Literasi Indonesia, 2026)
Shyness is a common personality trait experienced by college students during the transition to early adulthood, especially when facing the demands of social interaction in the college environment. This condition can affect students' ability to communicate, participate in academic activities, and build social relationships. This study aims to understand how the social environment influences the development of shyness in college students. The method used was a descriptive qualitative approach, with data collection techniques through in-depth interviews, observation, and documentation of three students with shy tendencies. The results indicate that a less supportive social environment, such as a lack of acceptance from peers, negative interaction experiences, and minimal emotional support, can strengthen shyness in college students. Conversely, an open, supportive, and secure social environment can help students increase self-confidence and reduce shy behavior. This study emphasizes the important role of the social environment in shaping student personality development, particularly in overcoming shyness, and provides implications for colleges to create a more inclusive and supportive environment for student social development.